Al-Mulāzima al-Fikrīyya bi Taṭbīqa al-Fiqih al-‘Aṣriyy - Muhammad Ishom (Al-Jami'ah: Journal of Islamic Studies, 1998)
Muslim jurists used to using the method of ijtihad to develop substantive legal aspects of Islamic law.   Later, the tradition of ijtihad becomes a means toward tajdid. The idiom of tajdid was well known in the time of Ibn Taymiyah where in the building of contemporary fiqh was gaining its moment. The effort to build such a framework of fiqh was also inspired by Yusuf al-Qardawi who asked the relevance of the product of fourteenth century ijtihad to   the current and future conditions. since we are all of the opinion that Islam is always relevant anywhere and anytime. Therefore, all mujtahids, are obliged to strife for keeping legal order with full understanding that legal thinking is always changing in accordance with the change of time. In general, the idea of the application of contemporary fiqh is led by three factors.  First.  Social interaction between Muslims and other people from different countries with varied culture; Second, the Western penetration to the Muslim world in many aspects of life; Third, the irrelevance of many legal decisions with the current problems due to the inclination of many jurists to standardize the understanding of Arab people in making law process. Understanding the fact, in the application of contemporary fiqh therefore one could not free himself from using the conventional methods of legal creation and understanding the objective of legal degree.